An extended sensor fault tolerant control method applied to three-phase induction motor drives - Huu Nguyen, Minh Chau; Tran, Cuong Dinh (Bulletin of Electrical Engineering and Informatics, 2024)
This research presents a fault tolerant (FT) control method for three-phase induction motor drives (IMDs) against sensor failures in the operating process. In this paper, an IMD applied the field oriented (FO) control for the speed and torque control is used to study the operation under sensor fault conditions. A fault detection isolation function is integrated into the FO control loop as an intermediary component to evaluate the quality of the measured signals of the sensors and provide proper signals for speed control of the drive system. A combined method of a comparison algorithm and a third difference operator (TDO) is proposed for the fault diagnosis function to improve the sustainable operation of the drive. The reliability of the proposed method will be verified through the operation mechanism of the FT function corresponding to three sensor fault states and a random noise state in the simulation environment by MATLAB/Simulink software.